The Influence Of Leadership Style And Work Discipline On Employee Performance At The Dukcapil Service Of Bengkulu City - Budiman, Aruf; Susanti , Neri; Yulianti , Oni (Universitas Dehasen Bengkulu, 2024)
The purpose of this study was to determine the effect of leadership style and work discipline on employee performance at the Dukcapil Service of Bengkulu City. The sample in this study was 30 civil servants at the Dukcapil Service of Bengkule City. Data collection using a questionnaire and the method of analysis used is multiple linear regression, determination test and hypothesis testing.The results of the regression analysis show Y = 2.888 + 0.206X1 + 0.882 X2, this illustrates a positive regression direction, meaning that there is a positive influence between X1 (leadership style) and X2 (work discipline) on performance (Y). Means that if the variables of leadership style and work discipline increase, performance will increase. Intelligence has a significant influence on employee performance at the Regional Secretariat of Lebong Regency because the significant value is 0.021, less than 0.05. Work discipline has a significant influence on employee performance at the Regional Secretariat of Lebong Regency because the significant value of 0.000 is less than 0.05. Leadership style and work discipline have a significant simultaneous influence on employee performance at the Regional Secretariat of Lebong Regency because a significant value of 0.000 is less than 0.05.